2018
DOI: 10.1504/ijtlid.2018.091800
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining user satisfaction of internet usage among public sector employees in Yemen

Abstract: Internet technology has become an essential technological tool for individuals, organisations, and nations driving growth and prosperity. However, there are countries such as Yemen which have very low internet usage rates and which see little economic, social and cultural progress as a result. Therefore, this study has developed an integrated conceptual model based the DeLone and McLean information systems success model (DMISM), the unified theory of acceptance and use of technology (UTAUT) and task-technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 76 publications
(165 reference statements)
0
18
0
Order By: Relevance
“…Little research efforts have been conducted to address this knowledge gap and investigated the relationship between the AU and total IT/IS benefits (Aldholay et al, 2018;Son et al, 2012). Earlier literature paid attention to the performance or/and net benefits of IS as an outcome construct (Isaac et al, 2016;Son et al, 2012). The current study attempts to bridge the gap as a contribution to academic knowledge; by investigating the connections between the "actual usage" and outcome constructs of the DQ and CQ.…”
Section: Relationship Between Outcome Variables (Communication Qualit...mentioning
confidence: 99%
“…Little research efforts have been conducted to address this knowledge gap and investigated the relationship between the AU and total IT/IS benefits (Aldholay et al, 2018;Son et al, 2012). Earlier literature paid attention to the performance or/and net benefits of IS as an outcome construct (Isaac et al, 2016;Son et al, 2012). The current study attempts to bridge the gap as a contribution to academic knowledge; by investigating the connections between the "actual usage" and outcome constructs of the DQ and CQ.…”
Section: Relationship Between Outcome Variables (Communication Qualit...mentioning
confidence: 99%
“…To measure behavioral intention, the scales from Venkatesh et al (2012) and Gefen et al (2003) were chosen. Finally, user satisfaction is measured by scales from Nguyen et al (2016) and Isaac et al (2018).…”
Section: Research Methodology Measurement Itemsmentioning
confidence: 99%
“…Thus, several empirical studies (Rahayu et al, 2019;Maillet et al, 2015;Zaied, 2015;Dalcher & Shine, 2003) put user satisfaction (US) as a dependent variable in the mandatory IS context of the public sector. US is defined as the degree to which users are satisfied with the decision to use the new technology because it meets their expectations (Isaac et al, 2018). US is one of the most widely used single measures of IS success to evaluate user response (DeLone & Mclean, 1992).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Meanwhile, others stated that perceived ease of use of any system could be more significant if the system perceived usefulness as well (Elkhani et al, 2014). Isaac et al (2016) performed a study on the relationship between perceived ease of use, perceived compatibility, and net benefits on an empirical study of internet usage among employees in Yemen and found that perceived compatibility was the prior factor when users used a system. Other research conducted by Hussain et al (2016) on perceived usefulness, perceived ease of use, and perceived enjoyment as drivers for the user acceptance of interactive mobile maps stated that users' acceptance of the interactive mobile maps was determined by three beliefs including perceived ease of use.…”
Section: Literature Reviewmentioning
confidence: 99%